Influence of Physical Workplace Factors on the Employees’ Performance in Organizations (A Case of Huduma Centre - Nyeri County) - Kagwi, Caroline Waithira (Human Resource and Leadership Journal, 2018)
Purpose: The purpose of this study was to investigate the influence of physical workplace factors on the performance of employees; a case study of Huduma Centre Kenya -Nyeri county. Methods: Descriptive research design was used and sample of 48 employees serving the 21 operational desks and 1 customer care desk was studied from the total population of 48 Huduma Centre-Nyeri County employees. During the study, data was collected from the respondents using questionnaires. Data analysis was done using Microsoft excel computer packages and information was presented through bar charts, tables and pie charts. Results: It was established that physical workplace aspects had a great contribution towards the organizations' performance in Huduma Centre, Nyeri County. Unique contribution to theory, practice and policy: Companies must comply with the environmental standards in all stages of a business development. The natural environmental factors affect the total costs of a firm in terms of equipment and assurance procedures to meet regulatory requirements.